Progress and Recent Developments in HIV Vaccine Research - Iris Shim; Lily Rogowski; Vishwanath Venketaraman (Vaccines)
Background: Human immunodeficiency virus (HIV) remains a global health challenge despite significant advancements in antiretroviral therapy and prevention strategies. Developing a safe and effective vaccine that protects people worldwide has been a major goal, yet the genetic variability and rapid mutation rate of the virus continue to pose substantial challenges. Methods: In this review paper, we aim to provide a comprehensive review of previous vaccine candidates and the progress made in HIV vaccine clinical trials, spanning from the late 1990s to 2025. PubMed and ClinicalTrials.gov were searched for English-language Phase 1–3 HIV vaccine trials published from 1990 to March 2025. After de-duplication, titles/abstracts and then full texts were screened; trial phase, regimen, immunogenicity, efficacy, and correlates were extracted into a structured spreadsheet. Owing to platform heterogeneity, findings were synthesized narratively and arranged chronologically to trace the evolution of vaccine strategies. Results: Early vaccine trials demonstrated that a protein subunit vaccine failed to protect against infection, revealing the complexity of HIV evasion strategies and shifting the focus to a comprehensive immune response, including both antibody and T-cell responses. Trials evaluating the role of viral vectors in generating cell-mediated immunity were also insufficient, and suggested that targeting T cell response alone was not enough. In 2009, the RV144 trial made a breakthrough by showing partial protection against HIV infection and providing the first indication of efficacy. This partial success influenced subsequent trials, prompting researchers to further explore the complex immune response required for protection and consider combinations of vaccine technologies to achieve robust, long-lasting immunity. Conclusion: Despite setbacks, decades of rigorous efforts have provided significant contributions to HIV vaccine discovery and development, offering hope for preventing and protecting against HIV infection. The field remains active by continuing to advance our understanding of the virus, refining vaccine strategies, and employing novel technologies.